Content Analysis (Analisis Isi) terhadap Peraturan Daerah Bernuansa Syariat Islam di Kabupaten Banyumas - Dody Nur Andriyan (Universitas Negeri Surabaya, 2019)
Regional Regulation (Perda) which regulates public issues such as prostitution, alcoholic beverages, gambling, and the relationship between men and women turns out to be identified as a Regional Regulation with nuances of Islamic law. in Banyumas Regency there is a Regional Regulation which if used by the identification of Arfiansyah above, it can be referred to as a Regional Regulation with nuances of Islamic law. The regulation is: Banyumas District Regulation Number 15 of 2014 concerning Control, Supervision and Control of Circulation of Alcoholic Beverages and Regional Regulations of Banyumas Regency Number 16 of 2015 concerning Community Disease Management. This research has two formulations of the first problem related to the results of the content of the analysis on the Perda that are nuanced by Islamic law in Banyumas Regency. Both of the results of the analysis content on the Regional Regulations that are nuanced by Islamic law in Banyumas Regency are not contrary to Law-Invitation Number 12 of 2011? This research is a qualitative-descriptive study. The research method used is normative juridical. The main source of data is the Banyumas District Regulation Number 15 of 2014 concerning Control, Supervision and Control of Circulation of Alcoholic Beverages and Regional Regulations of Banyumas Regency Number 16 of 2015 concerning Community Disease Management. Interviews were also conducted with resource persons. Furthermore, the results of the analysis were carried out. Regional Regulation No. 15 of 2014 is actually a Regional Regulation that has a broad purpose of public interest, for the nation and state. So that the claim that Perda No 15 of 2014 as a Regional Regulation with nuances of Islamic law is not true. Regional Regulation No. 16 of 2015 is actually a Regional Regulation that has a broad purpose of public interest, for the nation and state. So that the claim that Perda No 16 of 2015 as a Regional Regulation with nuances of Islamic law is not true. Both of these Perda (Perda No 15 of 2014 and Perda No. 16 of 2015) are not in conflict with Law No. 12 of 2011 concerning the Establishment of Legislation. Both in terms of content, principles, goals, arrangements, administrative sanctions and criminal sanctions. Formally and procedurally the two Perda are in accordance with Law Number 12 of 2011